TAZKIYATU Al-NAFS METHOD IN SHAPING THE MORALS OF LEARNERS IN PRIVATE HIGH SCHOOL TARBIYAH ISLAMIYAH HAMPARAN PERAK DISTRICT DELI SERDANG REGENCY - Harahap, Muhammad Yunan; Ependi, Rustam; Lubis, Sakban (Proceeding International Conference of Science Technology and Social Humanities, 2022)
Tazkiyatun Nafs is related to the purpose of human life, which is to obtain happiness both physically and spiritually. This happiness is the perfection of the soul, and the perfection of the soul itself depends on its purity. As for what hinders the perfection of the soul is the stain that is inflicted with ugly qualities. The purpose of this study is to find out how the application of the Tazkiyatu Al-Nafs method in forming student morals, then the method carried out in this study is qualitative in the field approach. While the result of this research is the success of Tazkiyatun Nafs Education in forming noble morals at MAS Tarbiyah Islamiyah Hamparan Perak can be shown by, First can be seen from Change behavior (Change of attitude, calmness) can control themselves from the luxuries of the world, then it is not easy to be emotional and calm in carrying out the learning process Second can be seen with the soul of students who are obedient in worship,  which is accompanied by an increase in the quality and quantity of worship to God, being punctual in carrying out obligatory worship and always maintaining the things that are prodded. Third, there is an attitude that arises in students in the form of being honest in speaking, polite manners to others, tawadhu, zuhud, qonaaah attitudes.